W świecie nonsensu i „Świerszczyka”, czyli bezdroża pseudonauki. Studium przypadku książki Aleksandry Kruszewskiej „Emocje, uczucia i społeczne zachowania emocjonalne dzieci na progu szkolnym” - Dorota Klus-Stańska (Problemy Wczesnej Edukacji)
The article is an attempt at a detailed analysis of the book on emotions, feelings and social behaviour of children starting school written by Aleksandra Kruszewska as a case of thickened errors in the theory, methodology and interpretation of collected empirical data. The book is an exemplification of the mechanisms of generating pseudoscience, both these which could occur in every discipline of science and those which are particularly typical of pedagogy.